Retrospective and Prospective View of Community Forestry in Nepal (Journal of Forest and Livelihood, 2003)
Community forestry in Nepal has gone through significant changes since its inception in the late 1970s. On one hand, impressive gains have been made in terms of developing and applying methodologies suitable for conditions in the Middle Hills. On the other hand, major challenges remain in terms of achieving equitable outcomes and in having community forests become significant engines for community development in forest-rich communities. The current political instability also requires a questioning of the appropriateness of the implementation modalities developed during more stable political times.